An Efficient Pulsed CH3OH Terahertz Laser Pumped by a TEA CO2 Laser - 纠智先 左都罗 苗亮 祁春超 程祖海 (Chinese physics letters, 2010)
An efficient pulsed CH3OH terahertz （THz） laser pumped by a TEA CO2 laser is investigated experimentally. To improve photon conversion efficiency and THz laser energy, two cavity configurations of the TEA CO2 laser, which is external and semi-external, are evaluated. The pump intensities are about 4.7 MW/cm2 and 1.2 MW/cm2, respectively. Higher pump intensity and more stable single lines are obtained in the external cavity. For the 3.8 J pump energy of the 9P（16） transition in the external cavity, the maximum terahertz output energy with 570.5 μm wavelength at 160 Pa is 431 μJ. With a 6 J energy pulse in terms of a semi-external cavity, a 353 μJ terahertz emission （570.5 μm） is produced. The corresponding photon conversion efficiencies are 1.36% and 0.705%, increasing by a factor of about 2.